Inventory Control of Vaccine Products in Pharmaceutical Company Using The Economic Order Quantity Model and Monte Carlo Simulation - Rahmadini, Nurhaliza; Supian, Sudradjat; Napitupulu, Herlina (International Journal of Global Operations Research, 2023)
Health is a basic need in human life. People spend a lot of money to maintain their health. One of the preventive health service options is to vaccinate. Indonesia is a country that can produce its own vaccines with its local pharmaceutical companies. The company faces stiff competition in today's rapidly growing market. Therefore, evaluation and assessment are needed to measure the progress of the company's development. One useful assessment is a company's financial review. Inventory control ensures that the planned approach can minimize costs without disrupting the production process. This research simulates data of demand and analyzes the inventory control based on simulated data. The object used in this research is the inventory of products of pharmaceutical companies. The data used is secondary data such as data of product quantity sold per period, purchasing cost, order cost, holding cost, shortage cost, and lead time. The method used for inventory control is Economic Order Quantity (EOQ) model and Monte Carlo simulation. The simulation results on the monthly demand for vaccine products show that the total demand for one year is 3.394.805 vials for Vaccine A, 1.320.900 vials for Vaccine B and 107.345 for Vaccine C. Based on simulated data processing, calculations using the probabilistic EOQ model result in total inventory costs of Rp.456.918.008.386,14 for Vaccine A, Rp 218.292.795.949,34 for Vaccine B, and Rp. 9.177.930.319,05 for Vaccine C.